An Investigation of Audit Expectation Gap in Indonesia’s Public Sector - Agus Joko Pramono; Riefqi Hanief (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2022)
The audit expectation gap has been studied since the early 1970s, and several approaches have been used to resolve this problem. However, such a gap persists both in the private and public sectors. Meanwhile, there are only a few studies related to this topic in the public sector, so the need to undertake more research in this area is encouraged. This study investigates to what extent the audit expectation gap occurs in Indonesia’s public sector. It also examines the effectiveness of the additional information in the audit report as mandated by the state financial auditing standards (SPKN, 2017) in closing the gap. A questionnaire was developed and administered to auditors, government officers, and students to capture their views. ANCOVA and Kruskal-Wallis were used to analyze the data collected from the questionnaires. The study discovered that the audit expectation gap in Indonesia’s public sector is related to the auditor’s responsibility. Such a gap is also found in frauds and errors in unqualified financial statements.